2020
DOI: 10.15761/icst.1000341
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of immune reconstitution and immune complications after cell and organ transplantation

Abstract: In this review, we have focused on immune restoration after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and solid organ transplantations (SOT). We discuss the kinetics of cytokine secretion during immune reconstitution phases that play a unique role in the connection between innate and adaptive immunity, therefore essential in normal and pathological immune reconstitution. We overview the importance of T cell immunity for antigen-specific immune reconstitution and the production of cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 114 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Multiple cellular alterations have been identified in cryptococcal meningitis IRIS (CM-IRIS), with the specific signature of blood granulocyte activation. In the setting of severe lymphopenia and immunosuppression, ineffective phagocytosis and antigen presentation lead to an increase in fungal burden and HIV viral load [47,48]. An increase in activated circulating neutrophils has been correlated with high mortality and can be considered a predictor of the degree of systemic oxidative stress and fatal outcomes [49].…”
Section: Cm-iris Cellulomics and Proteomicsmentioning
confidence: 99%
“…Multiple cellular alterations have been identified in cryptococcal meningitis IRIS (CM-IRIS), with the specific signature of blood granulocyte activation. In the setting of severe lymphopenia and immunosuppression, ineffective phagocytosis and antigen presentation lead to an increase in fungal burden and HIV viral load [47,48]. An increase in activated circulating neutrophils has been correlated with high mortality and can be considered a predictor of the degree of systemic oxidative stress and fatal outcomes [49].…”
Section: Cm-iris Cellulomics and Proteomicsmentioning
confidence: 99%
“…Different studies' interpretations differ in opinion with respect to the benefits and ability of HIV vaccines in activating endogenous single/double-stranded RNA sensing molecular machinery [45,46]. It has been shown that in patients with advanced HIV infection, the immune system functions in absence of a sufficient amount of cytokine interferon-gamma (IFNG), and the innate immune branch often exhibits exaggerated responses to antigenic stimulation [47,48]. Clinically, such responses are seen in the form of immune reconstitution inflammatory syndrome (IRIS) toward persistent antigens from previously treated opportunistic infections [49,50].…”
Section: Vaccines Against Human Immunodeficiency Virus Infectionmentioning
confidence: 99%
“…Clinically, such responses are seen in the form of immune reconstitution inflammatory syndrome (IRIS) toward persistent antigens from previously treated opportunistic infections [49,50]. Because they are not specific, vaccines can cause exaggerated systemic innate immune responses that lead to adverse events in immunocompromised individuals through activation and overexpression of TLR 3,7,8 OAS1-11, MDA1-5, IRFs, IFI, type 1 interferon genes, and the components of the inflammasome [49][50][51][52]. Adequate levels of interferon-gamma are necessary to establish appropriate virus-specific cytotoxic lymphocyte responses after therapeutic vaccination [53,54].…”
Section: Vaccines Against Human Immunodeficiency Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The future goal is to achieve targeted delivery, attune kinetics of mRNA expression, overcome cancer mutation rate, and reduce unintended host-immune reactions [17]. siRNA drugs has become invaluable in the field of transplantology, where life-saving hematopoietic stem cell transplantation is accompanied by numerous pre-and posttransplant complications [18,19]. One of the complications is hepatic veno-occlusive disease/sinusoidal obstructive syndrome (VOD/SOS), which has been successfully treated by the drug Defibrotide, which was formulated as a mixture of single-and double-stranded oligonucleotides [20].…”
Section: Applications Of Rna-based Therapeutics In Medicinementioning
confidence: 99%